Collective memory and industrial paternalism. working class population "sociedad explotadora de tierra del fuego", punta arenas, Chile Memoria colectiva y paternalismo industrial. el caso de la población obrera sociedad explotadora de tierra del fuego, punta arenas, Chile - Herrera O., Rodrigo; Matus Carrasco, Daniel Alejandro; Ambrosetti Garrido, Daniela Loredanna; Cvitanic Diaz, Boris Alejandro (My University, 2019)
Within the framework of expressions of industrial heritage in the south of Chile, the Sociedad Explotadora de Tierra del Fuego marked a presence that persists to this day in the city of Punta Arenas through the construction, in the 1950s, of a residential complex for the use of its workers and employees. An in-depth study of the Explotadora population, using blueprints and documentary archives, in addition to interviews and participatory workshops, gave an account of a social fabric that emerged from a particular urban and architectural proposal designed by the company, which remains alive in the memories and speeches of former and actual neighbors. The validity of this past in the present of its inhabitants informs about the paternalistic dynamics in the national industry, at their peak in the middle of the last century and that gradually declined from the 1980s onwards.
Keywords: collective memory; industrial paternalism; sociedad explotadora de tierra del fuego company; sociedad explotadora de tierra del fuego housing complex